Vitamin D enhances migration but decreases gene expression of vascular endothelial growth factor and tumor necrosis factor-α in Wharton’s jelly mesenchymal stem cells - Vitriyanna Mutiara Yuhendri; Nurfi Pratiwi; Ariza Julia Paulina; Ismawati Ismawati; Nicko Pisceski Kusika Saputra; Arfianti Arfianti (Universitas Nahdlatul Ulama Surabaya, 2025)
Mesenchymal stem cells (MSCs) have gained significant interest for their potential application in repairing damaged tissues through immunomodulatory functions. Vitamin D has been shown to regulate both the innate and adaptive immune systems. Active forms of Vitamin D, such as 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) are known to influence the action of mesenchymal stem cells (MSCs) in several mechanisms, such as stimulating their proliferation and osteogenic differentiation, as well as tissue regeneration. This study aimed to investigate the effects of vitamin D supplementation on the biological properties and expression of cytokines and growth factor genes in MSCs isolated from the human umbilical cord (UC). MSCs were isolated from Wharton’s jelly (WJ-MSC) of UC, cultured, and supplemented with various concentrations of vitamin D3. The Cell Counting Kit-8 (CCK-8) assay was used to measure cell viability, and a scratch wound healing assay was conducted to evaluate the migration capacity of MSCs. The mRNA expression levels of vascular endothelial growth factor (VEGF), tumor necrosis factor (TNF)-α, and interleukin (IL)-6 were quantified using reverse transcription-polymerase chain reaction (RT-PCR). This study showed that supplementation with 50 nM of vitamin D3 for 48 h significantly increased the viability and migratory capacity of MSCs. Furthermore, vitamin D supplementation significantly decreased the mRNA levels of TNF-α and VEGF but did not affect IL-6 gene expression compared to the control group. These findings suggest that vitamin D supplementation can enhance the biological characteristics and modulate the expression of key immunomodulatory factors in MSCs, potentially improving the effectiveness of MSC-based therapies.